STRATEGI PEMERINTAH KOTA JAMBI DALAM PENANGGULANGAN PENYALAHGUNAAN NARKOTIKA - Hapsa, Ratna Dewi (Jurusan Ilmu Sosial dan Ilmu Politik Fakultas Hukum Universitas Jambi, 2019)
Narcotics abuse becomes one of the National and even International issues which disturbs all circles, not only for the government but also the grassroots level of the lowest society, also feels the same. Evidenced by the disclosure of various cases ranging from smuggling to the capture of the drug network both revealed in the media and directly occur in the surrounding environment. Something similar happened in Jambi Province even the latest data (Tribun Jambi) mentions that Jambi Province ranks fourth in the National Narcotics abuse. The city of Jambi is in the first position for the level of Jambi Province, so according to the writer, it is necessary to have a policy on target from the City government to immediately cut off the chain of disgraceful activities, so that a strategic step is needed to realize the policy. This research uses a descriptive approach, with data collection techniques. interviews with members of the Jambi City BNN and Legal Bureau, along with other stakeholders. The results showed that the strategy and synergy between institutions, with three stages, namely prevention with a national campaign of the Prevention, Eradication, Abuse and Circulation Narcotics (P4GN) program, supervision with the strengthening of rehabilitation institutions in the City of Jambi, and legal actions with strengthening by all stakeholders involved. Keyword: Public Policy, Strategic Management, Narcotics Countermeasure, Jambi City